Multimodality Imaging for Cardiotoxicity: State of the Art and Future Perspectives. Issue 4 (October 2022) - Artico, Jessica; Abiodun, Aderonke; Shiwani, Hunain; Kurdi, Hibba; Chen, Daniel; Tyebally, Sara; Moon, James C.; Westwood, Mark; Manisty, Charlotte H.
Abstract: Modern cancer therapies have significantly improved survival leading to a growing population of cancer survivors. Similarly, both conventional and newer treatments are associated with a spectrum of cardiovascular disorders with potential long-term sequelae. Prompt detection and treatment of these complications is, therefore, pivotal to enable healthy survivorship and reduce cardiovascular morbidity. Advanced multimodality imaging is a valuable tool for stratifying patient risk, identifying cardiovascular toxicity during and after therapy, and predicting recovery. This review summarizes the potential cardiotoxic complications of anticancer therapies and the multimodality approaches available in each case with special focus on newer techniques and the added value of biomarkers ultimately leading to earlier diagnosis and better prognostication.